The effect of market segmentation on stock prices: The China syndrome - Sun, Qian; Tong, Wilson H.S. (Journal of Banking & Finance, 2000)
China has an A-share market that is open only to local investors and a B-share market that is open only to foreign investors. Contrary to what has been observed in other markets with a similar segmented structure, the China B shares trade at a discount relative to the A shares. We show that the phenomenon can still be explained by basic economic principles. Specifically, the existence of the H-share and the “red-chip” markets in Hong Kong provide good substitutes for the B-share market. We find that when more H shares and red chips are listed in Hong Kong, the B-share discount becomes larger. This is consistent with the model of differential demand elasticity proposed by Stulz and Wasserfallen (Stulz, R., Wasserfallen, W., 1995. Review of Financial Studies 8, 1019–1057).